Mendukung pendidikan berbasis kompetensi dengan program literasi dasar dan information literacy di perpustakaan sekolah - Nuryudi Nuryudi (Pusat Perpustakaan UIN Syarif Hidayatullah Jakarta, 2006)
Students are now living in information age and faced with a situation that is almost totally different with their parents at their ages. Information literacy skills are becoming important competency for them as well as for the teachers. Students need to be aware of their information necessities and know how to search, evaluate and wisely use the information for studies and their lives; Knowing how to learn effectively. However, actuating information literacy program requires the mastery of basic literacy - three fundamental areas of scaled-competencies utilized to succeed in the related various activities. Employing the program will be significant approach for school because it can be a gateway for the instution to develop community of learners within the information literate society and will be a substantial investment for future. Kata Kunci: Pendidikan berbasis kompetensi, literasi dasar, information literacy, perpustakaan sekolah